Fabrication of a biphasic scaffold for tissue engineering of intervertebral disc - Choy, Tsz-hang, Andrew. (The University of Hong Kong (Pokfulam, Hong Kong), 2013)
﻿Current treatments to intervertebral disc degeneration alter spine biomechanics and have complications. Tissue engineering offers an approach to regenerate a biological disc that provides flexibility and stability to, and integrates with the spine. To date, a scaffold that mimics the extracellular matrix composition and mechanical strength of a native disc is lacked. In this project, a biphasic scaffold was fabricated using glycosaminoglycan (GAG) and collagen, the prevalent ma-trix components in a native disc. It also adapted the structure of the disc, with la-mellae of collagen surrounding a collagen-GAG (CG) core. The first part of this project studied chemical modification of CG and evaluated the physiochemical and biological properties of modified CGs. As only loosely bound by GAG under physiological environment, collagen was modified by deamination, methylation and amination, and yielded Deaminated, Methylated and Aminated CGs upon co-precipitation with GAG. While GAG was mostly lost within 1 day in Untreated and Deaminated CGs, 20% and 40% GAG was retained after 6 days in Methylated and Aminated CGs respectively. In cell-seeded Aminated CG, over 60% GAG was retained after 8 days. Aminated CG, having the highest GAG/HYP of 4.5, best simulated the GAG-rich nucleus pulposus tissue. In ultrastructural analysis, Aminated CG consisted of abundant granular sub-stances that resembled the nucleus pulposus. Despite the differential initial number adhered to the CG scaffolds, human mesenchymal stem cells (hMSCs) had over 90% viability at all time points. Cell morphology was distinct, being round in Untreated and Methylated CGs but elongated in Deaminated and Aminated ones. The adhesion of hMSCs via collagen receptor, integrin alpha2beta1, was observed in all CG scaffolds, while adhesion via general matrix receptor, integrin alphaV, was extensive in all but Aminated CG. Based on improved GAG incor-poration and retention, which approximate the matrix composition of nucleus pulposus, Aminated CG was chosen as the core of the biphasic scaffold. The second part of this project studied lamination in biphasic disc scaffold and evaluated its mechanical properties in creep, recovery and dynamic loadings. A process was optimized to encapsulate a CG under physiological condition whilst producing an intact collagen gel, which allowed the CG to retain more GAGs and to be confined by the annulus structurally as was in the disc. This encasing approach was repeated for multiple lamellae, one lamella per day. Scaffolds with more lamellae had increased viscous compliance in creep and recovery, which was explained by the less laminated scaffolds being overloaded. Another lamination approach replaced most encasing lamellae with coiling ones. Despite low sample size, it was shown that this combined approach produced scaffolds with lower elastic and viscous compliances and longer equilibrating time in both creep and recovery, and higher complex modulus under dynamic loading. Full recovery was not achieved by any scaffold. This study demonstrated that a biphasic disc scaffold, made of GAG and collagen, contained similar matrix components to native disc, was almost mechanically comparable to the disc, and was cyto-compatible. It paved way towards tissue engineering of intervertebral disc and the intervertebral disc motion segment. === published_or_final_version === Mechanical Engineering === Doctoral === Doctor of Philosophy